Mathematics teachers’ Specialized Knowledge: A Case Study about Teaching of the Basic Concepts of Function - Rodríguez-Flores, Ariana (2018)
This research draws its attention to the specialized knowledge a secondary school teacher of mathematics demonstrates while teaching the basic concepts of function. This paper falls within the research field of teachers’ mathematical knowledge for teaching (Hill, Ball and Schilling, 2008). In addition, it uses didactic analysis (Gómez, 2007) to determine indicators that allow the identification and the characterization of this knowledge. The results show the richness of the conceptual structure taught when teaching, as well as the precise use of the mathematical language by the teacher, and the use of diverse systems of representation that emphasize the relation between them.